PERANCANAN JARINGAN KOMPUTER DENGAN MEMANFAATKAN VIRTUALISASI ROUTER (Information Technology and Telematics, 2015)
Abstract- Computer technology is growing rapidly ti inofation encourage people to continue and develop the existing technology. One development is done by add new features, storage space and a bigger processor. But in fact not all the features and facilities fully utilized, there are some empty storage space and not used. Virtualization can be one solution to utilize the remaining resources are not used, by creating a virtual machine. One of the devices that can be virtualized is a router. The router is a device in order to connect between different computer networks so that they can connect and communicate with each other directly. In a network to be built sometimes require more than one router, but the price is quite expensive can result greater spending. With the router virtualization it is expected to overcome these problems. Virtualize router it is as if we have two routers that can run simultaneously, can be given a different setting, and has full access to each router. Mikrotik routerOS is a router operating system of mikrotik that provides KVM features that can be used to virtualize the router. Keyword  : Virtualisasi, route, computer network, KVM